Religious Jewish Mothers as Music Mentors: Educating a New Generation of Ethical Listeners in the Age of Infinite Availability - Vaizman, Tal (Religious education, 2025)
This study explores how Orthodox Jewish-Israeli mothers use music as a tool for informal religious education in the home, navigating the challenges of the digital age. Through interviews with 27 mothers, our research reveals their strategies for curating soundscapes, managing age-appropriate content, and negotiating shared listening spaces. These practices reflect broader patterns in religious education, where music is used to reinforce values, shape cultural engagement, and foster intergenerational dialogue. The study highlights the evolving role of parents in maintaining religious identity amidst the digital abundance of contemporary media, emphasizing the intersection of music, values, and everyday religious life.